The fascist faith of the Legion "Archangel Michael" in Romania, 1927-41 - Iordachi, Constantin, author.
1 online resource.
Keywords: "The Fascist Faith of the Legion "Archangel Michael" in Romania, 1927-41 engages critically with recent works on fascism, totalitarianism, and religion, and advances an original theoretical and methodological approach to fascism as a political faith. On this basis, the book constructs an innovative comparative research framework for reconceptualizing the history of the Legion "Archangel Michael" in Romania, 1927-41. It contends that the Legion put forward a palingenetic political faith of a theological type, called legionarism. To provide a comprehensive analysis of the origins, main features, mechanisms of institutionalization and demise of this self-proclaimed salvific political faith, the book documents the palingenetic foundations of the Legionary faith, the syncretism between fascist and Christian rites and rituals, and the intricate relationship between the Legion and the Orthodox Church and its dogma. The book documents three main sacrificial strategies employed by the Legion to 're-evangelize' the people in the new faith: (1) the appropriation of the cult of the fallen soldiers; (2) terrorist missions meant to create fascist heroes through violent sacrifice; and (3) sanctification through heroic fight for Christianity in the Spanish Civil War, in an attempt to link legionarism with the transnational crusade against "Judeo-Bolshevism." As well as providing a detailed historical and interpretive account of the Legion, the book makes a significant contribution to debates about defining fascism and its relation to religion. It also provides novel comparative perspectives for studying other attempts at constructing fascist faiths in interwar Europe, most notably in Fascist Italy and Nazi Germany. This book will be of interest to students and scholars of fascism, politics and religion, political theory, Romanian history, youth radicalization, violence, and the emergence of terrorism"--